Pendekatan Pengkajian Agama (Teologis-Normatif) - Dafi Rasyid; Nova Azzahra; Maftuh Ajmain (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to explain the meaning of the theological-normative approach in Islamic studies, analyze the strengths and weaknesses of this approach, and describe its implementation in Islamic studies. The method used is library research with a descriptive-analytical approach to literature related to Islamic studies methodology. The results show that the theological-normative approach is a study of Islamic teachings from the perspective of normativity using the discipline of theology, which is classical, textual, and literal in nature. This approach has advantages such as being deductive and dogmatic, fostering strong love and loyalty to religion, cautious attitude, and adherence to religious guidance. However, this approach also has weaknesses, including tendencies toward exclusivity, closed-mindedness, fanaticism, intolerance, and difficulty distinguishing between sacred aspects and ijtihad. The implementation of this approach requires collaboration with other approaches, such as social approaches, to solve contemporary problems, especially in pluralistic societies like Indonesia.